Ag Week brings social media talk, Mar. 22 - Uribes, Tom::::::::: (2013)
Siskiyou County Farm Bureau President Jeff Fowle, will speak on 'Agriculture and Social Media,' 11 a.m. Friday, Mar. 22 in the Engineering East Building, Room 191.